GENERAL ACTEOSIDE OF REHMANNIAE LEAVES IN THE TREATMENT OF PRIMARY CHRONIC GLOMERULONEPHRITIS: A RANDOMIZED CONTROLLED TRIAL - Qiu, Hong Yu; Fan, Wenxing; Fu, Ping; Zuo, Chuan; Feng, Ping; Liu, Fang; Zhou, Li; Chen, Feng; Zhong, Hui; Liang, YaPing; Shi, Mei (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
The prospective, randomised, parallel controlled trial aimed to assess the efficacy and safety of Traditional Chinese Medicine – general acteoside of Rehmanniae leaves compared with piperazine ferulate in the treatment of primary chronic glomerulonephritis. A total of 400 patients diagnosed with primary chronic glomerulonephritis were recruited from outpatient clinics and were randomly assigned to the treatment group (general acteoside of Rehmanniae leaves, two 200mg tablets, bid) or the control group (piperazine ferulate, four 50-mg tablets, bid ). The primary outcome was 24-h urinary protein. Secondary outcome measures included evaluated glomerular filtration rate (eGFR), erythrocyturia, and electrolytes. After 8 weeks of treatment, the treatment group and the control group showed a mean reduction in 24-h proteinuria of 34.81% and 37.66%. The 95% CI of difference of the mean reduction in 24-h proteinuria between the two groups was [-11.50%, 5.80%]. No significant differences were found between the two groups in the erythrocyturia reduction. Neither group showed obvious changes between baseline and 8 weeks in eGFR or electrolytes. Adverse events occurred at a similarly low rate in the treatment group (1.5%) and control group (2.5%, P = 0.7238). Both general acteoside of of primary chronic glomerulonephritis.